User Satisfaction and Challenges in Plavon Dukcapil Online Services: Kepuasan Pengguna dan Tantangan dalam Layanan Dukcapil Online Plavon (Indonesian Journal of Cultural and Community Development, 2024)
General Background: The effectiveness of public administration services in Indonesia is crucial as the country transitions to digital platforms. Specific Background: This study examines the online services of Plavon Dukcapil in Rangkah Kidul Village, Sidoarjo Subdistrict, highlighting challenges faced by elderly users in navigating these services. Knowledge Gap: While existing research addresses the advantages of e-government, few studies focus on user satisfaction and effectiveness in rural areas, particularly regarding Plavon Dukcapil. Aims: This research aims to assess the effectiveness of Plavon Dukcapil's online services, focusing on community satisfaction related to service quality, speed, and accessibility. Results: Findings indicate that although service productivity aligns with regulations, efficiency is hindered by incomplete documentation and delays. Community satisfaction is compromised as many residents prefer in-person services over online options. Novelty: This study offers new insights into the operational challenges of e-government in rural Indonesia and highlights the need for improved community engagement. Implications: Enhancing communication and technical support for users, especially the elderly, could significantly improve the effectiveness and satisfaction of Plavon Dukcapil services, fostering better public service delivery in the digital era.Highlights:• Digital Transformation: The study emphasizes the role of technology in enhancing public service accessibility and efficiency.• Community Preferences: Many residents still prefer traditional in-person services over online platforms, indicating a gap in user experience.• Need for Engagement: Improved communication and support for vulnerable populations, particularly the elderly, are essential for increasing online service effectiveness.Keywords: Plavon Dukcapil, Online Services, Community Satisfaction, E-Government, Public Administration